A 24-Year-Old Female Transplant Recipient with Type 2 Membranoproliferative Glomerulonephritis and Disseminated Shingles: A Cautionary Tale of Deferring to Primary Care. (24th July 2021) - Burdorf, Benjamin T.
Abstract : In this report, the case of a 24-year-old Caucasian female with type 2 membranoproliferative glomerulonephritis status-post living donor kidney transplant managed on triple regimen immunosuppressive therapy who developed shingles is discussed. With its onset, she promptly reached out to her nephrologist who deferred her to primary care. Prior to seeing her primary provider, she developed disseminated herpes zoster. She consulted emergency services where she was given inadequate care and again deferred to primary care. One day later, the dissemination included her entire torso, face, oral cavity, and all extremities. Fortunately, the patient had the insight to again reach out to her nephrologist who arranged for her to be admitted for appropriate care 6 days after her initial inquiry that carried 6 days of zoster progression. This case demonstrates how it is pertinent that specialists recognize potentially lethal complications associated with the conditions they follow. Although convenient to defer to primary care, if specialists were to take on the responsibility of providing a broader scope of care for their unique subsets of patients, it would likely result in a reduction in the 80% of serious medical errors that occur as a result of miscommunication, or lack thereof, between care providers.